Chemometric Analysis for the Detection of Biogenic Amines in Chilean Cabernet Sauvignon Wines: A Comparative Study Between Organic and Nonorganic Production - Martinez-Fernandez, C; Ganga-Munoz, M; Yanez-Catalan, L (2012)
In this work, the presence of biogenic amines (BAs) was correlated with the type of wine grape culture (traditional or organic) and their concentration in the different stages of winemaking (must, alcoholic fermentation [AF] and malolactic fermentation [MLF]). The formation of BA occurred mainly during MLF in which the percentages for putrescine, cadaverine, phenylethylamine, histamine, and tyramine were 100%, 70%, 13%, 61%, and 44% for the wines produced with traditional grapes and 100%, 94%, 25%, 88%, and 13% for the wines produced with organic grapes, respectively. In general, these latter wines exhibited a lower concentration of total amines. The principal component analysis and partial least-square discriminate analysis indicated that the generation of BA has a certain behavioral pattern in the wines analyzed, which is associated with the different stages of wine production and with the type of culture (traditional or organic) used in the wine grapes. © 2012 Institute of Food Technologists®.